Early Treatment of Depressive Symptoms and Long‐Term Survival After Liver Transplantation. Issue 4 (20th February 2013) - Rogal, S. S.; Dew, M. A.; Fontes, P.; DiMartini, A. F.
<x xml:space="preserve">Abstract</x> While depression after liver transplantation (LTX) is associated with decreased survival, the effects of treating depression remain unknown. We assessed a previously described, prospective cohort of 167 patients transplanted for alcohol‐related liver disease from 1998 to 2003. Depressive symptoms were measured with the Beck Depression Inventory serially throughout the first posttransplant year. Adequacy of antidepressant treatment was measured with the Antidepressant Treatment History Form. Using Cox‐proportional Hazards modeling, survival times were assessed for recipients with no depression versus depression with adequate medications versus depression with inadequate medications. Seventy‐two recipients had depressive symptoms in the first posttransplant year. Of these, 43% (n = 31) received adequate pharmacotherapy and 57% (n = 41) received inadequate (n = 7) or no pharmacotherapy (n = 34). After a median follow‐up time of 9.5 years, 32% of the inadequately treated depressed group survived versus 52% of the adequately treated group and 56% of the nondepressed group (p = 0.006). Compared to the nondepressed group, those with adequately treated depression had no significant difference in survival. However, recipients with depression and inadequate pharmacotherapy had decreased survival times compared to nondepressed recipients (HR for death = 2.44, 95% CI = 1.45, 4.11), controlling for other known confounders. The factor most strongly linked to long‐term mortality after liver transplantation in this cohort was untreated depression.